Bone mineral density in elite male and female cyclists at different stages of a professional cycling career - Hilkens, L.; Weijer, V. C. R.; van Schijndel, N.; Boerboom, M.; van der Burg, E.; Kempers, R.; Peters, V.; Bons, J.; van Loon, L. J. C.; van Dijk, J. W. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Bone health appears to be compromised in many elite male cyclists, while bone health in female, adolescent and retired, elite cyclists remaining largely unexplored. The lack of osteogenic stimuli and low energy availability may predispose elite cyclists to impaired bone health, although clear evidence for this presumption is lacking. In the present study we assessed the prevalence of low bone mineral density (BMD) in male and female elite cyclists at different stages of a professional cycling career, and evaluated potential predictors of low BMD in elite cyclists.